The environmental state under pressure - Mol, A. P. J.; Buttel, Frederick H. (Amsterdam : JAI, 2002)
For a long time in industrialized countries the state occupied a comfortable and unquestioned position in dealing with environmental problems. Since the 1960s we have witnessed the rather smooth institutionalization of environmental tasks in state policies and politics, leading to the emergence of the "environmental state". In the 1980s, the ideologies of deregulation and privatization formed the start of the debate on the environmental state and the 1990s left the debate facing new challenges. First, the debate became broader and more sophisticated, moving away from simple deregulation and privatization arguments and toward the issue of political modernization and reinventing government. Second, in addition to the ongoing debate on the environmental state within national boundaries, the processes of and political debates on globalization led to new challenges in the viability of the (nationally ordered) environmental-regulatory state. Third, the debate widened geographically, from Europe and the North American continent to the central and East-European countries undergoing transition away from centrally planned economies with all-dominating states, and to states in the so-called South. Various analytical frameworks and social theories are now being applied to understanding and evaluating the nature of these social processes, transformations and continuities related to the environmental state. This text provides a thorough examination of these issues with particular emphasis on the treadmill-of-production and the ecological modernization perspectives. The volume draws upon case studies and evidence from environmental states in the North American continent, Western Europe, Africa, Southeast and East Asia and Central and Eastern Europe.
The environmental state under pressure: an introduction / Arthur P.J. Mol and Frederick H. Buttel -- The treadmill of production and the environmental state / Allan Schnaiberg, David N. Pellow and Adam Weinberg -- Ecological modernization and the environmental state / Arthur P.J. Mol and Gert Spaargaren -- From the treadmill of production to ecological modernization? Applying a Habermasian framework to society-environment relationships / Dana R. Fisher -- State policies: to improve air quality / Allan Mazur and Eric W. Welch -- Environmental governmentality as a basis for regulatory reform: the adaptation of new policy instruments in Finland / Rauno Sairinen -- European union as a suprastate in agri-environmental issues: the Finnish perspective / Pekka Jokinen -- Environmental discourse and the state: a social analysis of debates on transport and environment on transport and environment in Portugal and the Netherlands / C.S.A. (Kris) Van Koppen -- Environmental state and the forest: of lookouts, lumberjacks, leopards, and losers / Bianca Ambrose-Oji ... [et al.] -- Global in the local: the environmental state and the management of the Nile perch fishery on Lake Victoria / Douglas C. Wilson -- Deforestation, floods, and state reactions in China and Thailand / Graeme Lang -- Motivating a conflicted environmental state: community-driven regulation in Vietnam / Dara O'Rourke -- Environmental state in constant transition: decentralization and economization in Russia / Olga Aksenova and Valeriy Nedelkov.
Includes bibliographical references.
Description based on print version record.
Keywords: Environmental policy; Environmental ethics; Environmental quality; Central government; Social impact of environmental issues; Political Science -- Public Policy -- Environmental Policy